Antibacterial poly(vinylidene fluoride)-based melt-blends. (January 2023) - Woo, Insun; Lee, Jong In; Han, Dong Je; Han, Dong-Heon; Oh, Seung-Ju; Yoon, Jae Uk; Choi, Soon-Mok; Sohn, Eun-Ho; Bae, Jin Woo
Abstract: Although poly(vinylidene fluoride) (PVDF) is widely used in the preparation of biomedical devices, bacterial growth on the polymer surfaces reduces the functionality and lifetime of these devices. To overcome this issue, pyridinium group grafted-PVDF (Pyd-PVDF) was added to PVDF. We prepared antibacterial PVDF-based blends with large-quantities through melt-blending of the PVDF and Pyd-PVDF using a twin-screw extruder. The structural, thermal, mechanical, and antibacterial properties of the prepared blends were characterized. The Izod impact strengths and elongations of the antibacterial PVDF-based blends increased with increasing Pyd-PVDF concentration. In contrast, the flexural moduli and tensile strengths slightly decreased with increasing Pyd-PVDF concentration. This is ascribed to the higher intermolecular interactions between PVDF and Pyd-PVDF as well as lower crystallinity of antibacterial PVDF-based blends as a function of Pyd-PVDF. When the antibacterial activities of the blends were determined against E. coli growth, the blends with ≥5 wt% of Pyd-PVDF exhibited 99.99% antibacterial activities. Highlights: Large-quantities of antibacterial PVDF/Pyd-PVDF blends were prepared by melt-blending. Intermolecular interactions & crystallinity of blends affected mechanical properties. Impact strengths and elongations of the blends increased with addition of Pyd-PVDF. Flexural moduli and tensile strengths of the blends slightly decreased. ≥ 5 wt% of Pyd-PVDF blends exhibited 99.99% antibacterial activity against E. coli .